Holocaust cinema complete : a history and analysis of 400 films, with a teaching guide - Brownstein, Rich 1962- (McFarland & Company, Inc., Publishers, 2021)
Narrative Holocaust film basics -- Stats and eras -- Surprising Holocaust film traits -- The unavoidables : Elie Wiesel, Anne Frank, Oskar Schindler and Oscar Bait -- A practical history of Holocaust filmmaking in Hollywood -- The greatest narrative Holocaust film ever made -- Roman Polanski and The pianist (2002) -- Holocaust film curriculum planning : the "SOFTA" system -- Recommended Holocaust films -- Epilogue : Eva.Stories and Holocaust film trend